1976
DOI: 10.1007/bf00286857
|View full text |Cite
|
Sign up to set email alerts
|

Sunshine and the geographical distribution of the alleles of the Gc system of plasma proteins

Abstract: Following the discovery by Daiger et al. (1975) that the Gc proteins of human plasma act as the carriers of vitamin D, the authors have plotted on a world map all available data on the frequency of the allele Gc2, and compared the distribution with that of sunlight. With some exceptions high frequencies of Gc2 correspond to low levels of sunlight and vice versa. Similar comparisons within Ireland show no such relation. The results are discussed in relation to natural selection and the incidence of rickets, due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…Walter and Steegmtiller (1969) have reported that GC*2 frequencies tend to decrease from north to south in the Old World. Mourant et al (1976) frequency from north to sourth in the Chinese populations (Nakajima and Ohkura, 1971) is well-explicable by the above hypothesis. Another explanation may be given that such a cline was formed by gene flow in past spreads of populations acquiring high GC*2 frequency in dull climates.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Walter and Steegmtiller (1969) have reported that GC*2 frequencies tend to decrease from north to south in the Old World. Mourant et al (1976) frequency from north to sourth in the Chinese populations (Nakajima and Ohkura, 1971) is well-explicable by the above hypothesis. Another explanation may be given that such a cline was formed by gene flow in past spreads of populations acquiring high GC*2 frequency in dull climates.…”
Section: Resultsmentioning
confidence: 60%
“…Data on the racial and geographical variations of GC allele frequencies have been accumulated and analyzed (Walter and Steegmtiller, 1969;Mourant et aL, 1975Mourant et aL, , 1976.…”
Section: Introductionmentioning
confidence: 99%
“…This diverse historical affiliations of the tribal groups could be one of the factors to account for the genetic diversity seen here, but at the same time a possible role of a yet unknown selection cannot be ruled out. Mourant et al [1976] proposed an inverse correlation of Gc*2 allele with the degree of insolation, and more recently a direct correlation was suggested with Gc*lF al lele [Papiha, 1986], Matsumoto et al [1980] proposed a selection due to skin pigmen tation as a possible explanation to account for the variation of Gc frequencies be tween Mongoloid populations from North and South-east Asia. Such variation of pigmentation, although not yet studied in India, is quite visible in tribal popula tions from North-west, North-east and South India.…”
Section: Resultsmentioning
confidence: 99%
“…Anthropologists, interested by genetic relationships analyses of human populations and the study of their evolutionary history, have initially used classic genetic markers such as those of ABO blood groups (Mourant et al, 1976), the PI system of alpha 1 antitrypsin (for review see Denden et al, 2012), HLA loci, Rhesus system (e.g., Sanchez-Mazas and Langaney, 1988;Chaabani et al, 2000;Arnaiz-Villena et al 2010) and particularly those of immunoglobulin GM system known by its unparalleled ability, of a single system, to differentiate human populations (Chaabani, 2002). These studies have demonstrated that the gene pool is not a simple sum of genes, but is a dynamic system, which is hierarchally organized and which maintains the memory of past events in the history of populations.…”
Section: Molecular Anthropologymentioning
confidence: 99%